TWO-WORD VERBS DALAM ALBUM STAND UP AND SCREAM OLEH ASKING ALEXANDRIA - SAINO, RIFCKY (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study is an attempt to find out the forms and analyze the meaning of “Two-Word Verbs in the Album Stand Up and Scream by Asking Alexandria. The data were analyzed based on the theories of Coghill (2003: 114) and McCarthy and O’Dell (2007: 6). The method used in this research was descriptive method. The data of two-word verbs were taken from the lyrics in the album Stand Up and Scream by Asking Alexandria. The result of this study shows that there are 61 of two-word verbs found in the 15 songs, there are categorized into 3 forms based on the theory of Coghill (2003: 114) Transitive separable two-word verbs (there are 43 forms), Transitive inseparable two-word verbs (there are 14 forms) and Intransitive two-word verbs (there are 4 forms). Based on the theory of Randall (1982: 330), each two-word verbs has it’s own means. Keywords: Two-word verbs, Transitive & intransitive phrasal verbs, Asking Alexandria.